Jawabanmu

2014-04-20T19:12:44+07:00
lim h->0 (f(x+2h)-f(x))/h! = lim h->0 3(x+2h)² - 3x³
                                                         h
                                  = lim h->0  3(x² + 4xh + 4h²) - 3x²
                                                            h                                
                                 =
lim h->0 3x² + 12xh + 12h  - 3x²
                                                            h
                                 =
lim h->0 h(12x + 12)
                                                     h
                                 = lim h->0 (12x + 12)
                                 = 12(0) + 12
                                 = 0 + 12
                                 = 12
Jadi,
lim h->0 (f(x+2h)-f(x))/h = 12